Media-oriented digital communication and techno wellness in the academic online context: Exposure to risky digital content - Z. Halalsheh, Niveen; Jubrail Qaqish , Ghada; Khaled Mohmmad Saeed Al Salahat, Yasmeen; faris salem batarseh, Leen (Research Journal in Advanced Humanities, 2025)
This study aimed to investigate the interplay between media-oriented digital communication and Techno Wellness within the academic online context, focusing specifically on students’ exposure to risky digital content, such as electronic blackmail. The primary objective was to examine the relationship between electronic blackmail anxiety and its impact on Techno Wellness among students enrolled in the Faculty of Educational Sciences at the University of Jordan. Employing a descriptive correlational design, the study surveyed a sample of 350 male and female students using two validated and reliable instruments: the Techno Wellness Scale and the Electronic Blackmail Anxiety Scale. Findings revealed a moderate level of Techno Wellness alongside a high level of electronic blackmail anxiety among the participants. Moreover, results indicated a statistically significant negative correlation between electronic blackmail anxiety and Techno Wellness. The study concludes by emphasizing the urgent need to design awareness programs addressing the psychological and academic risks of exposure to harmful digital practices, evaluate preventive strategies, and encourage the integration of digital tools that promote mental well-being in academic contexts. Further recommendations highlight the importance of enhancing inter-institutional collaboration, developing precise assessment instruments, and advancing research in the field of digital communication and Techno Wellness.